Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2147/ccid.s77742
|View full text |Cite
|
Sign up to set email alerts
|

Antiaging, photoprotective, and brightening activity in biorevitalization: a new solution for aging skin

Abstract: BackgroundAge-related changes in the dermis can be considered the result of intrinsic factors and the consequence of environmental damage, mainly due to ultraviolet (UV) radiation from the sun (responsible for skin photoaging). The great versatility of the mesotherapy “biorevitalization” lies in the synergy between different biological effects of the active injected substances, which treats the skin in a more complete way. Several studies about biorevitalization efficacy showed good results. To date, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 16 publications
3
40
0
3
Order By: Relevance
“…The growing interest to maintain a youthful appearance prompted the development of new dermatological procedures for treatment of skin aging. In recent years, there has been an increasing emphasis on minimally invasive treatments and techniques designed to treat volume loss, wrinkles, and skin photodamage . Such procedures include mesotherapy and autologous PRP .…”
Section: Discussionmentioning
confidence: 94%
“…The growing interest to maintain a youthful appearance prompted the development of new dermatological procedures for treatment of skin aging. In recent years, there has been an increasing emphasis on minimally invasive treatments and techniques designed to treat volume loss, wrinkles, and skin photodamage . Such procedures include mesotherapy and autologous PRP .…”
Section: Discussionmentioning
confidence: 94%
“…Positive changes in the appearance of the facial skin after HA treatment (improved firmness and pigmentation) were observed by Landi et al 35 Trong et al 36 also documented improved skin elasticity and wrinkle depth reduction, while Baspeyras et al, 37 observed significant improvement in skin hydration, firmness and viscoelasticity after HA microinjection treatment. A statistically significantly improved radiance, pigmentation and hydration were observed by Sparavigna et al, 38 in the process of treating skin with symptoms of ageing and photoaging.…”
Section: Discussionmentioning
confidence: 80%
“…The injected mixture was able to have an action on the skin pigmentation process with a photoprotective effect [19]. One can assume that antioxidants, particularly ascorbic acid [18] [20], niacinamide [21] and GSH [22] have skin whitening properties.…”
Section: Discussionmentioning
confidence: 99%